2018
DOI: 10.1111/jocn.14249
|View full text |Cite
|
Sign up to set email alerts
|

Benefit finding for Chinese family caregivers of community‐dwelling stroke survivors: A cross‐sectional study

Abstract: This study offers nurses rational for assessing caregiver's negative emotions and benefit finding. By targeting benefit finding, the nurse may guide caregivers in benefit identification and implement interventions to reduce anxiety, depression and caregiver burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…First, the scale provides a tool to measure the benefit finding of caregivers during acute and chronic phases of stroke recovery. Caregivers with a low level of benefit finding may be identified as a risk factor for negative outcome, requiring further assistance and resources (10). Second, the scale provides a tool to further study the mechanism of benefit finding and the experience of family caregivers, which includes both negative and positive experiences (48).…”
Section: Implications For Clinical and Research Practicementioning
confidence: 99%
“…First, the scale provides a tool to measure the benefit finding of caregivers during acute and chronic phases of stroke recovery. Caregivers with a low level of benefit finding may be identified as a risk factor for negative outcome, requiring further assistance and resources (10). Second, the scale provides a tool to further study the mechanism of benefit finding and the experience of family caregivers, which includes both negative and positive experiences (48).…”
Section: Implications For Clinical and Research Practicementioning
confidence: 99%
“…Open access researchers have shown that the greater the level of benefit perceived by caregivers is, the lower the level of caregiver burden and depression; thus, identifying these benefits finding could play a moderating or mediating role in the relationship between caregiver burden and depression. [18][19][20] In addition, the perception among caregivers of a higher level of benefits would also help care recipients. 21 Hence, identifying these benefits finding may provide a new direction for providing psychological care for caregivers of stroke survivors from the positive view.…”
mentioning
confidence: 99%
“… 20 Mental health-care personnel should pay special attention to the “Caregiver Benefit Finding” that enhance positive emotion of caregivers, thereby improving the perception of care-giving burden and family functioning. 43 …”
Section: Discussionmentioning
confidence: 99%